The clinical manifestations and interval changes of reverse-transcriptase quantitative polymerase chain reactions among different specimens of coronavirus disease 2019 patients. Issue 2 (29th October 2020) - Chen, Po-Liang; Hsiao, Yi-Han; Chuang, Chien; Feng, Jia-Yih; Ho, Hsiang-Ling; Lin, Yi-Tsung; Chen, Su-Jung; Huang, Shiang-Fen; Chen, Hsin-Pai; Chou, Teh-Ying; Chen, Yuh-Min; Wang, Fu-Der
Abstract : Background: Since December 2019, a number of cases and deaths due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic have been reported worldwide. In spite of clinical manifestations similar to the SARS-CoV epidemic in 2003, affected organs and severity are yet to be defined. Moreover, viral load alterations and viral shielding among different specimens remained scarce. Therefore, clarifying clinical presentations and correlations among viral loads, disease severity, and viral shielding of SARS-CoV-2 infection is crucial in the disease prevention. Methods: The clinical courses of SARS-CoV-2 cases were presented through Gantt charts. Laboratory examinations and reverse-transcriptase quantitative polymerase chain reactions (RT-qPCR) among different specimens were tested periodically. Cycle thresholds (CT ) were recorded and presented as viral loads. Results: From March 2020 to April 2020, 4 SARS-CoV-2 cases were presented, of which, cases 1 and 2 manifested the symptoms severer than cases 3 and 4, along with higher serum lactate dehydrogenase levels and graded for lymphocytopenia. Case 4 initially exhibited anosmia but recovered within a short period. Curves of the CT of all the cases, except case 2, concaved upward after prescribing hydroxychloroquine (HCQ) and azithromycin. Except for case 4, the CT in most stool specimens remained undetectable; however, none of the cases presented gastrointestinal symptoms. Surprisingly, the CT values of the saliva specimens were inconsistent with those of the nasopharyngeal swabs and sputum. Conclusion: SARS-CoV-2 manifests various symptoms. Sudden onset of central nervous system symptoms should be considered. The timing of HCQ and azithromycin administration might be a key factor in the viral load reduction. Positive prediction values of RT-qPCR of different specimens should be tested carefully to prevent false-negative results.